Atomistic Understanding of the Ferroelectric Properties of a Wurtzite‐Structure (AlN)n/(ScN)m Superlattice. Issue 5 (26th February 2021) - Ye, Kun Hee; Han, Gyuseung; Yeu, In Won; Hwang, Cheol Seong; Choi, Jung-Hae
Abstract : For ferroelectric applications, wurtzite (WZ)‐phase (Al, Sc)N is investigated using ab initio calculations. The key ferroelectric properties, such as the ferroelectric switching barrier and spontaneous polarization, are examined in (AlN) n /(ScN) m superlattice (SL) structures by varying the ScN fraction, and compared with an (Al, Sc)N solid solution (SS). The reduction of the switching barrier is dominated by the local structural instability rather than the flattening of the buckled monolayer composed of metal–nitrogen pairs in WZ‐stacking. This argument is supported by the doping effects of other metal elements as well as the reduction of the switching barrier in the SL, which does not accompany the flattening of the buckled monolayer. The decrease in the spontaneous polarization along the ScN fraction is explained by structural parameters (the in‐plane area and the buckling parameter) and the Born effective charge (BEC). The slight decrease in the spontaneous polarization in the SL is attributed to the larger increase in the in‐plane area rather than the BEC. In contrast, the decrease in the buckling parameter in the SS is suggested to more significantly reduce the spontaneous polarization along the ScN fraction. Abstract : The ferroelectric properties (switching barrier [ E a ] and spontaneous polarization [ P s ]) of (AlN) n /(ScN) m superlattice structures are investigated and compared with those of (Al, Sc)N solid solutions, based on density functional theory calculations. The E a and P s values decrease as the ScN fraction increases, which are attributed to the structural parameters and local structural instability.